2021
DOI: 10.3399/bjgp.2020.1118
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting primary care practitioners’ alcohol-related discussions with older adults: a qualitative study

Abstract: Background: Risk of harm from drinking is heightened in later life, due to age-related sensitivities to alcohol. Primary care services have a key role in supporting older people to make healthier decisions about alcohol. Aim: To examine primary care practitioners’ perceptions of factors that promote and challenge their work to support older people in alcohol risk-reduction. Design and Setting: Qualitative study consisting of semi-structured interviews and focus groups with primary care practitioners in Norther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 42 publications
0
2
0
4
Order By: Relevance
“…Other studies have shown that poor adherence to screening for alcohol and physical activity are thought to be a result of limited training, lack of confidence or time, concerns about the impact on the practitioner-patient relationship, and patient compliance [ 5 , 7 , 8 ]. Practitioners perceive alcohol screening to be a sensitive topic for older individuals, adding concerns about stigma, particularly for individuals who consume more than the recommend guidelines [ 9 ]. Those engaged in heavy drinking are also perceived to be more likely to lie about their alcohol consumption, and are less supportive of routine screening for alcohol intake than those who drink less [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown that poor adherence to screening for alcohol and physical activity are thought to be a result of limited training, lack of confidence or time, concerns about the impact on the practitioner-patient relationship, and patient compliance [ 5 , 7 , 8 ]. Practitioners perceive alcohol screening to be a sensitive topic for older individuals, adding concerns about stigma, particularly for individuals who consume more than the recommend guidelines [ 9 ]. Those engaged in heavy drinking are also perceived to be more likely to lie about their alcohol consumption, and are less supportive of routine screening for alcohol intake than those who drink less [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Given these barriers, practice nurses -who are often experienced in assessment, preventive care, and brief interventions -may be well-positioned to support or carry out these activities concerning older men's alcohol use. 84 In Australia, almost two-thirds (64%) of alcohol and other drug services clients receiving alcohol treatments are male, 85 suggesting these services may be particularly accessible for men. Practitioners and services such as these specialised alcohol services, mental health practitioners, community-based programs, and support groups may play important roles in caring for older men engaging in problematic alcohol use; however, little is known about the appeal and efficacy of these avenues for older men.…”
Section: Discussionmentioning
confidence: 99%
“…Outras barreiras incluíam identificar o consumo de risco e não saber intervir, responsabilizar exclusivamente os idosos pela prevenção à saúde e atribuir o uso "moderado" de álcool como aceitável (CHAN et al, 2021). A presença de obstáculos ao se movimentar na comunidade, a incapacidade de lidar com recursos financeiros , a falta de tempo devido as exigências de outras demandas de cuidado na APS e os desafios de integrar uso de instrumentos específicos para idade na rotina de trabalho também podem contribuir para efeitos negativos no cuidado em relação ao álcool (BAREHAM et al, 2021;DIBARTOLO;JAROSINSKI, 2017;MOORE, 2018;LAL;PATTANAYAK, 2017).…”
Section: Intervenção Breve Para áLcool Em Idososunclassified
“…A compreensão dos principais riscos associados ao consumo de álcool e das barreiras à mudança podem tornar mais eficazes a triagem e a intervenção breve para o idoso (HAN; MOORE, 2018). Dado o envelhecimento da população que faz consumo de risco de álcool, são urgentemente necessárias intervenções personalizadas, proativas e multidimensionais (BAREHAM et al, 2021). Essas ferramentas contribuirão para reduzir os comportamentos de risco, minimizar o início e as consequências graves do consumo de álcool, prevenir recaídas e sensibilizar os idosos que apresentam dificuldades em procurar ajuda (DIBARTOLO; JAROSINSKI, 2017) ou que não tem acesso regular aos serviços na APS .…”
Section: Intervenção Breve Para áLcool Em Idososunclassified
See 1 more Smart Citation